Large drought-induced variations in oak leaf volatile organic compound emissions during PINOT NOIR 2012. (March 2016) - Geron, Chris; Daly, Ryan; Harley, Peter; Rasmussen, Rei; Seco, Roger; Guenther, Alex; Karl, Thomas; Gu, Lianhong
Abstract: Leaf-level isoprene and monoterpene emissions were collected and analyzed from five of the most abundant oak ( Quercus ) species in Central Missouri's Ozarks Region in 2012 during PINOT NOIR ( Particle Investigations at a Northern Ozarks Tower – NOx, Oxidants, Isoprene Research ). June measurements, prior to the onset of severe drought, showed isoprene emission rates and leaf temperature responses similar to those previously reported in the literature and used in Biogenic Volatile Organic Compound (BVOC) emission models. During the peak of the drought in August, isoprene emission rates were substantially reduced, and response to temperature was dramatically altered, especially for the species in the red oak subgenus ( Erythrobalanus ). Quercus stellata (in the white oak subgenus Leucobalanus ), on the other hand, increased its isoprene emission rate during August, and showed no decline at high temperatures during June or August, consistent with its high tolerance to drought and adaptation to xeric sites at the prairie-deciduous forest interface. Mid-late October measurements were conducted after soil moisture recharge, but were affected by senescence and cooler temperatures. Isoprene emission rates were considerably lower from all species compared to June and August data. The large differences between the oaks in response to drought emphasizes the need to consider BVOC emissions at the species level instead of just the whole canopy. Monoterpene emissions from Quercus rubra in limited data were highest among the oaks studied, while monoterpene emissions from the other oak species were 80–95% lower and less than assumed in current BVOC emission models. Major monoterpenes from Q. rubra (and in ambient air) were p-cymene, α-pinene, β-pinene, d -limonene, γ-terpinene, β-ocimene (predominantly1, 3, 7-trans-β-ocimene, but also 1, 3, 6-trans-β-ocimene), tricyclene, α-terpinene, sabinene, terpinolene, and myrcene. Results are discussed in the context of canopy flux studies conducted at the site during PINOT NOIR, which are described elsewhere. The leaf isoprene emissions before and during the drought were consistent with above canopy fluxes, while leaf and branch monoterpene emissions were an order of magnitude lower than the observed above canopy fluxes, implying that other sources may be contributing substantially to monoterpene fluxes at this site. This strongly demonstrates the need for further simultaneous canopy and enclosure BVOC emission studies. Highlights: Leaf level Isoprene emission factors for 4 of 5 oaks were significantly reduced during a severe drought. Quercus stellata leaf isoprene increased during the drought period. Leaf isoprene response to increasing temperature was impacted for most oak species. The leaf BVOC emission data supports findings at the canopy level, but discrepancies for monoterpene emissions remain.